2011
DOI: 10.1007/s12070-011-0343-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified Technique of Anterior Nasal Packing: A Comparative Study Report

Abstract: Anterior nasal packing, which is a common procedure in otorhinolaryngology practice, has different complications. Pain during introduction and removal of pack, bleeding after removal due to mucosal damage and synechia formation are common among them. A continuous effort is going on worldwide to combat those by modifying the nature of pack material or inventing new materials for nasal packing. In the present study an effort was made to compare a new modification of conventional gauze pack by using aluminum foil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
(7 reference statements)
0
15
1
Order By: Relevance
“…6 Dutta et al conducted a study on techniques of anterior nasal packing in epistaxis., found that 93.33% patients with gauze packing for epistaxis experienced severe pain (score 8-10), whereas in our study 52% patients had a pain score over 8. 7 Schoenberg et al in their study on nasal packing after routine nasal surgery observed a mean pain score of 5.7 as compared to 1.4 in patients in whom splints were used. 8 Nunez et al did study on nasal packing against septal suturing, found worse pain scores in the nasal packing group than patients who underwent mucosal suturing and have concluded nasal packing is not absolutely necessary after septal surgery.…”
Section: Discussionmentioning
confidence: 95%
“…6 Dutta et al conducted a study on techniques of anterior nasal packing in epistaxis., found that 93.33% patients with gauze packing for epistaxis experienced severe pain (score 8-10), whereas in our study 52% patients had a pain score over 8. 7 Schoenberg et al in their study on nasal packing after routine nasal surgery observed a mean pain score of 5.7 as compared to 1.4 in patients in whom splints were used. 8 Nunez et al did study on nasal packing against septal suturing, found worse pain scores in the nasal packing group than patients who underwent mucosal suturing and have concluded nasal packing is not absolutely necessary after septal surgery.…”
Section: Discussionmentioning
confidence: 95%
“…xylometazoline [18]. Seify et al [5] [15,24]. No study has compared the pain associated with cotton swab and merocele packing.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior nasal packing (ANP), a frequently performed procedure in the management of epistaxis, has potential complications, including discomfort during placing and removing the pack and rebleeding following removal owing to mucosal injury and synechia formation . As such, more optimal treatment strategies are needed for the management of epistaxis, especially for patients taking antiplatelet drugs.…”
mentioning
confidence: 99%